Pendidikan Lanjutan di Era Global: Sosialisasi dan Kesadaran Masyarakat Desa Batah Barat, Madura - Aziz, Muhammas Tareh; Rido'i, Muhammad (Pusat Penelitian dan Pengabdian Masyarakat STIQ ZAD Cianjur, 2025)
The development of the global era demands improvements in the quality of human resources through continuing education as a foundation for national progress. This community service program is highly urgent because it contributes to raising awareness of the importance of continuing education for the community in Batah Barat Village, Madura. The goal is to increase community understanding and motivation to actively participate in lifelong education. The community service method uses a participatory approach through outreach, interactive discussions, and collective reflection so that participants not only receive information but also engage in discussions about local solutions. The results of the activity indicate a high level of motivation in the community's understanding of the benefits of continuing education, especially in facing global challenges in the fields of employment, technology, and digital literacy. This new activity focuses on integrating digital literacy into the socialization of continuing education, which has an impact on policy recommendations for increasing access to and participation in education at the village level.Keywords: globalization, public awareness, further education.